2020
DOI: 10.1002/ccd.28800
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of bivalirudin versus heparin in transradial coronary interventions

Abstract: Objectives: We sought to evaluate the efficacy and safety of bivalirudin versus heparin in patients with coronary artery disease undergoing transradial artery coronary intervention (TRI). Background: Bivalirudin and radial artery access are independently associated with improved cardiovascular outcomes. However, data supporting a strategy of combining both to achieve additive improvements in cardiovascular outcomes provide conflicting results. Methods: A systematic search was performed to identify randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…A meta-analysis in 2016 by Mina et al suggested that bivalirudin reduces bleeding risk only with femoral access [ 44 ]. Furthermore, in a recent updated meta-analysis by Kheiri et al examining bivalirudin in patients undergoing transradial PCI, bivalirudin compared with heparin ± glycoprotein IIb/IIIa inhibitors was associated with a reduced risk of net adverse clinical events; however, there was no significant difference in the risk of major bleeding at 30 days [ 45 ]. A significant reduction in major bleeding was only observed compared with heparin + planned glycoprotein IIb/IIIa inhibitors [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis in 2016 by Mina et al suggested that bivalirudin reduces bleeding risk only with femoral access [ 44 ]. Furthermore, in a recent updated meta-analysis by Kheiri et al examining bivalirudin in patients undergoing transradial PCI, bivalirudin compared with heparin ± glycoprotein IIb/IIIa inhibitors was associated with a reduced risk of net adverse clinical events; however, there was no significant difference in the risk of major bleeding at 30 days [ 45 ]. A significant reduction in major bleeding was only observed compared with heparin + planned glycoprotein IIb/IIIa inhibitors [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a recent updated meta-analysis by Kheiri et al examining bivalirudin in patients undergoing transradial PCI, bivalirudin compared with heparin ± glycoprotein IIb/IIIa inhibitors was associated with a reduced risk of net adverse clinical events; however, there was no significant difference in the risk of major bleeding at 30 days [ 45 ]. A significant reduction in major bleeding was only observed compared with heparin + planned glycoprotein IIb/IIIa inhibitors [ 45 ]. However, most trials examined in these meta-analyses did not randomise patients according to procedural access, and there may have been confounding factors that were unaccounted for [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that hirudin can inhibit increased EC permeability ( Chen et al, 2020 ); however, hirudin has not been clinically recommended because it has not been available in adequate amounts. Increasing new evidence has suggested that patients treated with bivalirudin show reduced rates of hemorrhage compared to those treated with unfractionated heparin in many procedures in which anticoagulation is needed, such as transradial coronary interventions ( Kheiri et al, 2020 ), emergency percutaneous coronary intervention (PCI) for acute myocardium infarction ( Han et al, 2015 ), especially emergency interventional therapy for elderly individuals ( Meng et al, 2020 ), implantation of a left ventricular assist device ( Bates et al, 2020 ) and cardiac surgery in children ( Goswami et al, 2020 ) . There are currently no reports on whether bivalirudin can inhibit the changes in EC permeability induced by thrombin.…”
Section: Introductionmentioning
confidence: 99%
“…Kheiri et al provide an aggregate (study‐level) data network meta‐analysis of bivalirudin versus heparin in the transradial access subgroups of PCI randomized trials 1 . While there is a significant decrease in net adverse cardiovascular events (NACE) with bivalirudin versus heparin (6.3 vs. 7.4%) at 30 days, there is no significant difference in long‐term ischemic, bleeding, or NACE between bivalirudin and heparin.…”
mentioning
confidence: 99%